Highly effective treatment of bacterial infection-accompanied wounds by fat extract-embedded phototherapeutic hydrogel - Haonan Wang; Yingnan Xiao; Deli Zhuge; Genghe Shi; Chengping Liu; Hui Liang; Jing Wu; Yunxuan Huang; Yilin Xie; Chunnan Hu; Jiafeng Xie; Xinyi Wang; et al. (Journal of Nanobiotechnology)
Abstract Phototherapy presents an effective approach for treating localized methicillin-resistant Staphylococcus aureus (MRSA) infections; however, the tradeoff between therapeutic efficacy and negative off-target effect persists. To address these issues, we have developed a nanoparticle-hydrogel superstructure comprising phototherapeutic liposomal nanobubbles (NB) and fat extract (FE) encapsulated by F-127 hydrogel. After local administration to sites of MRSA infection, the superstructure effectively neutralizes high levels of MRSA toxins to protect against toxin-mediated cytotoxicity through loaded, which can also be leveraged to enhance anti-MRSA efficacy via toxin-regulated on-demand phototherapy upon near-infrared irradiation. Meanwhile, the oxidative stress-induced injury to healthy cells can be mitigated by the FE. In a murine model of skin MRSA infection, treatment with the nanoparticle-hydrogel superstructure significantly reduces MRSA load, especially when combined with MRSA toxin for enhanced bacterial inhibition. Concurrently, this superstructure accelerates wound healing by enhancing angiogenesis and collagen deposition while reducing inflammation. Overall, the nanoparticle-hydrogel superstructure shows promise for treating local pathogen-infected wounds.